Exploring Medical Check-Up Behaviors for Early Detection of Non-Communicable Diseases Among Diponegoro University Students - Aurytha, Vierelsha Avara Divani; Prabumurti, Priyadi Nugraha; Handayani, Novia (Faculty of Public Health, Universitas Diponegoro, Semarang, Indonesia, 2024)
AbstractIntroduction: Indonesian Basic Health Research (Riskesdas) in 2018 showed that the prevalence of high blood pressure at the age of >18 years increased from 25.8% to 34.1%, obesity at the age of >18 years increased from 14.8% to 21.8%, and smoking prevalence at the age of >18 years increased from 7.2% to 9.1%. This study analyzed the medical check-up behavior to detect non-communicable diseases on Diponegoro University students.Methods: This research was a quantitative research with a cross-sectional research method. This research was conducted in August 2024. Total 400 people were chosen using quota sampling technique. Data collection was carried out using Google Form. The dependent variable was medical check-up behavior and the independent variables were perception of susceptibility, severity, benefits, barriers, cues to action, and self-efficacy.Data analysis of the association used chi square tests.Results: The majority of the respondents were aged ≥ 21 years old, female, and come from a non-health faculty. A quarter of the subjects or 101 students (25,3%) had a medical check-up without a doctor’s referral. There was no association between perceived susceptibility, severity, benefit, barrier, cues to action, self-efficacy and medical check-up behavior.Conclusion: There was no association between perception of susceptibility, severity, benefits, barriers, cues to action, and self-efficacy and medical check-up behavior among Diponegoro University students. It is important to raise students’ awareness on the importance of medical check-ups.